Detection Rates of Cortical Auditory Evoked Potentials at Different Sensation Levels in Infants with Sensory/Neural Hearing Loss and Auditory Neuropathy Spectrum Disorder - Gardner-Berry, Kirsty; Chang, Hsiuwen; Ching, Teresa Y. C.; Hou, Sanna (Seminars in Hearing, 2016)
With the introduction of newborn hearing screening, infants are being diagnosed with hearing loss during the first few months of life. For infants with a sensory/neural hearing loss (SNHL), the audiogram can be estimated objectively using auditory brainstem response (ABR) testing and hearing aids prescribed accordingly. However, for infants with auditory neuropathy spectrum disorder (ANSD) due to the abnormal/absent ABR waveforms, alternative measures of auditory function are needed to assess the need for amplification and evaluate whether aided benefit has been achieved. Cortical auditory evoked potentials (CAEPs) are used to assess aided benefit in infants with hearing loss; however, there is insufficient information regarding the relationship between stimulus audibility and CAEP detection rates. It is also not clear whether CAEP detection rates differ between infants with SNHL and infants with ANSD. This study involved retrospective collection of CAEP, hearing threshold, and hearing aid gain data to investigate the relationship between stimulus audibility and CAEP detection rates. The results demonstrate that increases in stimulus audibility result in an increase in detection rate. For the same range of sensation levels, there was no difference in the detection rates between infants with SNHL and ANSD.
Keywords: Cortical auditory evoked potentials; auditory neuropathy spectrum disorder; infants